The Impact Of TQM On Customer Satisfaction: An Empirical Analysis Of Service Organizations In Malaysia. - Yi, Sit Wen (2008)
The main purpose of this study was to investigate the relationship between TQM practices and customer satisfaction, from the managers' perspectives. It was proposed that the six TQM dimensions, namely (i) leadership, (ii) strategic planning, (iii) customer focus, (ii) process management, (v) information and analysis, and (vi) human resource focus would facilitate the level of customer satisfaction of TQM certified service organization in Malaysia.